2016
DOI: 10.1371/journal.pone.0159870
|View full text |Cite
|
Sign up to set email alerts
|

White Adipose Tissue Browning in the R6/2 Mouse Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is a fatal, autosomal dominantly inherited neurodegenerative disorder, characterised not only by progressive cognitive, motor and psychiatric impairments, but also of peripheral pathology. In both human HD and in mouse models of HD there is evidence of increased energy expenditure and weight loss, alongside altered body composition. Unlike white adipose tissue (WAT), brown adipose tissue (BAT), as well as brown-like cells within WAT, expresses the mitochondrial protein, uncoupling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The formation of beige cells in WAT has been observed in several transgenic mouse strains with a lean, reduced-adiposity phenotype [34,50]. In this study, we collected histological and gene expression data that provided evidence of WAT browning accompanied by a reduced body fat percentage in Tks4-KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of beige cells in WAT has been observed in several transgenic mouse strains with a lean, reduced-adiposity phenotype [34,50]. In this study, we collected histological and gene expression data that provided evidence of WAT browning accompanied by a reduced body fat percentage in Tks4-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected from two Tks4-KO and two WT samples, and the results are represented on a logarithmic scale. The differentially expressed genes were grouped according to their gene ontology similarities and clustered into pro-adipogenic, anti-adipogenic, and pro-brown functional groups [34]. We extracted the PPARγ target genes from the differentially expressed genes with the help of the PPARgene database, which lists the experimentally verified and computationally predicted PPARγ target genes [35].…”
Section: Methodsmentioning
confidence: 99%
“…Alongside muscle atrophy, an altered body composition, accompanied by dysfunctional adipocytes, has been described in several HD mouse models 12 , 52 54 , and expression of mutant huntingtin in adipocytes has been shown to result in altered adipocyte function, such as reduced triglyceride storage within the adipocytes 53 . A feature of the HD hyper catabolic state has been suggested to be an abnormal fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The ghrelin‐induced decrease in energy expenditure observed for R6/2 mice was likely related to ghrelin‐mediated modulation of the sympathetic nervous system . It has previously been suggested that R6/2 mice display increased sympathetic nervous tone, shown by increased browning of WAT …”
Section: Discussionmentioning
confidence: 88%